Efeitos da infecção por Ancylostoma ceylanicum em hamster (Mesocricetus auratus): avaliação da carga parasitária e da coinfecção por Schistosoma mansoni - Luciana Ribeiro Serafim (2014)
Hookworm infections constitute a serious public health problem in many parts of the world, including Brazil. Patients presents different aspects of the disease burden, which may be related to the parasite load and/or associations with other parasites, as the endemic areas for this parasite are overlapping with others parasitic diseases. Therefore, this study aimed to evaluate two aspects of infection with Ancylostoma ceylanicum in hamster; the first related to the parasite load and the second related to the co-infection with the parasite Schistosoma mansoni. In the assessment of parasitic burden A. ceylanicum increasing inocula of the L3 larvae (25, 75, 125and 250) were used, and the animals followed for 21 days for the evaluations of weight, number of eggs in the faeces, blood count, humoral response, histopathological analysis of the small intestine and morphometry of adult worms. The averages of adult worms recovered were: 28, 0%; 24, 8%; 24, 6% and 24, 8% according to the number of third stage larva used to inocula size of 25, 75, 125 and 250 L3, respectively. The size of the inoculum did not affect the establishment, survival or fecundity of adult helminthes. Reductions in the red blood cell and hemoglobin levels in the infected group were correlated inversely with the number of white blood cells. Moreover, differential cell counting revealed a positive correlation between the worm load and leucocytes numbers. The humoral response against excretory-secretory antigens was more robust and sensitive compared with the response against crude extract, with no positive correlation with the number of worms. The effect of the population density was more evident in female worms with a reduction of the width of the females from the group infected with 250 L3 in comparison to the 25 L3 group. An inverse correlation relationship between inoculum and weight of the animals was observed. The second part of the study was to evaluate the influence of coinfection with S. mansoni in hamsters. Two experiments were conducted by switching the order of infection. Weight were assessed, the elimination of eggs in the feces, blood count, humoral response (IgG), histopathological analysis of the small intestine and morphology of granulomas. It was observed that the chronology of infection influenced the results in relation to weight loss in coinfected groups. When the A. ceylanicum preceded infection by S. mansoni animals showed the same weight reduction observed in the group infected only by A. ceylanicum, which did not occur in coinfection preceeded by S. mansoni. Although A. ceylanicum and S. mansoni are bloodsucking worms, no exacerbation of anemia in the coinfected groups were observed. The establishment of the second infection was not affected by prior infection in any of the experiments. It was not observed a positive correlation between the amount of S. mansoni eggs retained in the liver or eliminated in the faeces with the production of anti-SEA IgG. In general the production of IgG to the group Sm + Acey was lower in comparison to the Sm group. The co-infection did not influence the formation, development and evolution of granulomas in the small intestine of infected hamsters.